A pocketbook of hair and scalp disorders : an illustrated guide - Gray, John; Dawber, R. P. R (Blackwell Science, 1999)
Proctor & Gamble, Middesex, UK. Pocket-sized text discussing hair and scalp disorders. Addresses the physiology of hair and hair defects, examination, assessment and treatment, and dermatological disorders. For general practitioners. High-quality color photographs. Trim size: 8.5 x 4.5 inches. DNLM: Hair Diseases handbooks.
Keywords: dermatózy skalpu; Hair Diseases; kožní nemoci; nemoci vlasů; dermatovenerologie; Skin Diseases; Scalp Dermatoses